2020
DOI: 10.1186/s13568-020-00975-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of low-temperature adapted GH5-CBM3 endo-cellulase from Bacillus subtilis 1AJ3 and their application in the saccharification of switchgrass and coffee grounds

Abstract: Endocellulase is a key cellulase for cellulosic material pretreatment in the industry by hydrolyzing long cellulose chains into short chains. To investigate the endocellulase characteristics from Bacillus subtilis 1AJ3, and increase its production yield, this paper cloned an endocellulase gene denoted CEL-5A from strain 1AJ3 and expressed in E. coli BL21 (DE3). The CEL-5A gene was sequenced with a full-length of 1500 bp, encoding a totally of 500 amino acids, and containing two domains: the GH5 family catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
4
19
0
1
Order By: Relevance
“…Among the tested substrates, Cel M displayed the maximum specificity with β‐ d ‐glucan and the cellulose derivative, Na‐CMC (Table 1). This was in accordance with many previous reports on endoglucanases characterized from different sources (Guerrero et al, 2020; Ma et al, 2020; Wang et al, 2019; Yin et al, 2020). A limited activity was measured in the presence of galactomannan‐containing substrates, for example, Locust bean gum and Guar gum.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Among the tested substrates, Cel M displayed the maximum specificity with β‐ d ‐glucan and the cellulose derivative, Na‐CMC (Table 1). This was in accordance with many previous reports on endoglucanases characterized from different sources (Guerrero et al, 2020; Ma et al, 2020; Wang et al, 2019; Yin et al, 2020). A limited activity was measured in the presence of galactomannan‐containing substrates, for example, Locust bean gum and Guar gum.…”
Section: Resultssupporting
confidence: 94%
“…The kinetic parameter values, K m , k cat , and k cat /K m , of Cel M toward Na-CMC were computed as 19.87 mg mL −1 , 138 s −1 , 101.5 mg mL −1 s −1 , respectively. The kinetic analysis determined a fairly good substrate affinity of Cel M , which was comparable to that of the previously characterized GH5 endoglucanases from T. rubra YIM 77501 (Yin et al, 2020), B. subtilis 1AJ3 (Ma et al, 2020), and oil reservoir (Zhu et al, 2020). The turnover number and enzyme efficiency of Cel M were more or less similar to that of previously reported endoglucanases from termite microbiome (Guerrero et al, 2020) and cow rumen metagenome (Patel et al, 2020).…”
Section: Kinetic Parametersupporting
confidence: 81%
See 1 more Smart Citation
“…It was related to a GH family cellulase from B. velezensis by the BLASTx program. This putative endoglucanase was classified as an endoglucanase belonging to the GH5 family, which is the largest and most functionally diverse family of endoglucanases detected in numerous species [91][92][93]. The phylogenetic tree showed that this putative endoglucanase was clustered with the endoglucanases from B. amyloliquefaciens, B. siamensis, B. subtilis, B. thuringiensis, and B. velezensis.…”
Section: Discussionmentioning
confidence: 97%
“…A estabilidade térmica em alta (60°C) e baixa (30-50°C) temperatura é um recurso desejável para a aplicação industrial de celulases, pois economiza energia da reação (Ma et al, 2020), e permite a interação com outras enzimas, tais como aquelas que degradam lignina (a 30°C) e xilanases (a 50-60°C) (Liu et al, 2019).…”
Section: Drentensis Me-2)unclassified